Effect of the combination of Education level and Business location on product quality: The Case Study of Arc Welding in Small Scale Metalworking Enterprises in Kenya - Ondieki, Charles M. M. (Archives of Business Research, 2019)
The quality of products from the micro and small enterprise sector is affected by both the entrepreneur’s and enterprise’s attributes. This paper presents and discusses findings of a study that was designed to investigate experimentally the relationship between the quality of arc in the Small Scale Metalwork sub-sector and the combined effect of the artisan’s education level and business location. A total of 36 artisans with secondary education and 36 artisans with primary education consisting of formally (35) and informally (37) trained artisans from urban (29) and rural (43) areas participated in the evaluation. A mild steel product was fabricated by each participating artisan, assessed and scores awarded based on the quality of arc welding. The analysis of variance (ANOVA) was used to show any variation in the quality of arc welding; comparisons of means using the Least Significant Difference (LSD) at the alpha level of 5% were done to determine which pairs of artisans affected quality significantly. The study found out that artisans with secondary education performed better than those with primary education. The study also found out that artisans from urban areas performed better those from rural areas. The findings of this study provide evidence that higher level of education and urban location of business can improve product quality.